Analysis of Information Technology Application in The Quotation Unit PT Asuransi Sinar Mas Using Cobit 5 Framework - Richad Agustinus Kusuma D; Yani Rahardja; Melkior Nikolar Ngalumsine Sitokdana (Politeknik Pertanian Negeri Samarinda, 2020)
The application of information technology in an organization can add value to effectiveness and efficiency in achieving organizational goals, therefore it is necessary to assess the management of information technology in the organization. Analysis of the application of information technology in this research using the COBIT 5 framework which focuses on the subdomains BAI04, BAI09, and MEA01. Assessment of the application of information technology in the Quotation Unit division at PT. Asuransi Sinar Mas, which already using information technology in every business process carried out in the division. The overall result of the application of technology in the Quotation Unit division reaches level 3 (Defined Level). From the results obtained, recommendations were made for the Quotation Unit division to reach the level desired by PT. Sinar Mas Insurance is level 4 (Managed) so that it can support the organization in achieving the goals in terms of information technology.